Sexually transmitted infections in the elderly: an integrative review (Research, Society and Development, 2023)
The term "Sexually Transmitted Infections" refers to conditions, curable or not, that are caused by about 30 viruses, bacteria and other infectious agents. In developing countries such as Brazil, an individual aged 60 years or older is considered elderly. The objective of this study was to evaluate which factors predispose to Sexually Transmitted Infections in the elderly population. This study is framed within an integrative literature review research, based on the following phases: recognition of the theme and the distinction of the research question; organization of exclusion and inclusion criteria; consolidation of chosen studies; distribution of elected works; observation of research, results and finally, the review of the study. Thus, the studies were published in the years 2017 to 2022, with the equivalent of 33.3% in the year 2017, 33.3% in the year 2020, 16.6% in the year 2021 and about 16.6% % in the year 2022. Furthermore, most of the works were from Brazil - 50%, against 16.6% from Japan, 16.6% from China and 16.6% from Italy. In view of the above, it was observed that the elderly population is constantly vulnerable to sexually transmitted infections, where it was evidenced that STIs are showing increasingly alarming numbers in this age group, with emphasis on female elderly. For future research, it is recommended that there be more initiatives for scientific research that address the issue, as the aging process requires more articulations that are made possible through scientific research, thus providing a better quality of life for the elderly.